2019
DOI: 10.1111/sms.13486
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal force production and multi‐segment foot kinematics during the acceleration phase of bend sprinting

Abstract: This paper investigated horizontal force production, foot kinematics, and metatarsophalangeal (MTP) joint push‐off axis use during acceleration in bend (anti‐clockwise) and straight‐line sprinting. It was hypothesized that bend sprinting would cause the left step push‐off to occur about the oblique axis, resulting in a decrease in propulsive force. Three‐dimensional kinematic and ground reaction force data were collected from nine participants during sprinting on the bend (36.5 m radius) and straight. Antero‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(69 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Nine male sprinters (mean age ± 4 years; body mass 71.48 ± 9.47 kg; stature 1.81 ± 0.06 m) with experience of bend sprinting (200 and /or 400 m) volunteered to participate in this study. The sample size was guided by previous bend sprinting literature (Alt et al, 2015;Churchill et al, 2015;Churchill et al, 2016;Judson et al, 2019) and the number of available skilled athletes meeting the inclusion criteria of the study. To standardise ability with previous research (Alt et al, 2015, 22.60 ± 0.33 s; Churchill et al, 2015, 22. sprints.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine male sprinters (mean age ± 4 years; body mass 71.48 ± 9.47 kg; stature 1.81 ± 0.06 m) with experience of bend sprinting (200 and /or 400 m) volunteered to participate in this study. The sample size was guided by previous bend sprinting literature (Alt et al, 2015;Churchill et al, 2015;Churchill et al, 2016;Judson et al, 2019) and the number of available skilled athletes meeting the inclusion criteria of the study. To standardise ability with previous research (Alt et al, 2015, 22.60 ± 0.33 s; Churchill et al, 2015, 22. sprints.…”
Section: Participantsmentioning
confidence: 99%
“…To standardise ability with previous research (Alt et al, 2015, 22.60 ± 0.33 s; Churchill et al, 2015, 22. sprints. For the identification of gait events, a force plate (Kistler, Model 9287BA, 900 x 600 mm) was embedded into the track surface at approximately m. For full details of the experimental set-up, please refer to Judson et al (2019).…”
Section: Participantsmentioning
confidence: 99%
“…The aforementioned research reported that performance in a standardized curve sprint test has a limited relationship with straight sprinting and suggested that these abilities are different and independent physical qualities [11]. This notion can be reinforced by observing the differences in body position, force application, joint angles, and running mechanics when athletes sprint in linear or curvilinear trajectories [15][16][17][18][19][20]. For example, it is known that contact time in the inside leg (IL) is higher than in the outside leg (OL) [16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Statistical parametric mapping (SPM) (Pataky, 2010) is being used in many contemporary biomechanics studies to compare biomechanical time series data between conditions (Colyer, Nagahara, & Salo, 2018;Judson et al, 2019;Pataky et al, 2008;Warmenhoven et al, 2018). SPM allows the data to be compared along the whole time series and not just for key discrete data points, i.e.…”
Section: Statistical Parametric Mappingmentioning
confidence: 99%
“…maximum and minimum values of a the centre of pressure data during walking may obscure or reverse statistical trends compared to using SPM to compare the whole time series centre of pressure data (Pataky et al, 2014). Judson and co-workers also highlighted the benefit of using SPM when they compared left and right foot ground reaction forces in bend sprinting -SPM identified asymmetries between left and right foot mediolateral forces for parts of the stance phase (Judson et al, 2019).…”
Section: Statistical Parametric Mappingmentioning
confidence: 99%